If ageing is a disease, then life is also a disease - Chmielewski, Piotr Paweł; Strzelec, Bartłomiej (Anthropological Review, 2020)
Ageing is distinct from a disease. Sound arguments have been adduced to explain that senescence cannot be understood as a pathological process. Nevertheless, this distinction is believed to be artificial (Holliday 1995), and other eminent researchers argue that the senescence-pathology dichotomy is also misleading. Recently, it has been suggested that ageing should be classified as a complex pathological syndrome or a ‘pre-disease’ that is treatable. Proponents of this new paradigm argue that: (i) modern evolutionary theory predicts that ‘although organismal senescence is not an adaptation, it is genetically programmed’, (ii) ‘insofar as it is genetically determined, organismal senescence is a form of genetic disease’ (Janac et al. 2017) and (iii) ‘ageing is something very much like a genetic disease: it is a set of pathologies resulting from the action of pleiotropic gene mutations’ (Gems 2015). Also new generations of researchers, free of these traditional shackles, come with the belief that it is time to classify ageing as a disease, as the distinction between normal dysfunction and abnormal dysfunction is not completely clear and should be abandoned. Although they marshal their arguments in a convincing manner, persuasive counterarguments can be mounted. Here, the senescence-pathology dichotomy is critically discussed. A deeper analysis of this subject reveals the underlying problem of undefined terminology in science.